2020
DOI: 10.1101/2020.08.26.267864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of the cAMP levels with a conserved actinobacteria phosphodiesterase enzyme reduces antimicrobial tolerance in mycobacteria

Abstract: Antimicrobial tolerance (AMT) is the gateway to the development of antimicrobial resistance (AMR) and is therefore a major issue that needs to be addressed.The second messenger cyclic-AMP (cAMP), which is conserved across all taxa, is involved in propagating signals from environmental stimuli and converting these into a response. In bacteria, such as M. tuberculosis, P. aeruginosa, V. cholerae and B. pertussis, cAMP has been implicated in virulence, metabolic regulation and gene expression. However, cAMP signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The gene rv1339 is highly conserved in TB bacilli (Supplementary Fig. 13) and other mycobacteria and a recent study revealed that the Rv1339 protein degrades cAMP, an important signalling molecule controlling peptidoglycan metabolism 13 . Inactivation of rv1339 or expression of the mutated rv1339 allele from KC9A1 increased stress resistance in M. canettii STB-D and STB-K and reduced envelope permeability in M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene rv1339 is highly conserved in TB bacilli (Supplementary Fig. 13) and other mycobacteria and a recent study revealed that the Rv1339 protein degrades cAMP, an important signalling molecule controlling peptidoglycan metabolism 13 . Inactivation of rv1339 or expression of the mutated rv1339 allele from KC9A1 increased stress resistance in M. canettii STB-D and STB-K and reduced envelope permeability in M. smegmatis.…”
Section: Discussionmentioning
confidence: 99%
“…An identical nucleotide substitution C>T at nucleotide position 1582889, corresponding to the gene BN42_21248, was found in all clones recovered after cycle 6 (Supplementary Table 1). This mutation changed a single amino acid P96L in the protein it encodes, which is the orthologue of Rv1339, a MTB H37Rv protein, which was recently shown to encode a phosphodiesterase degrading cyclic-AMP (cAMP) 13 (Fig. 2a).…”
Section: Small Numbers Of Mutations Were Fixed In the Populations Dur...mentioning
confidence: 99%
“…We have previously linked Rv1339 mutations to resistance to other QcrB inhibitor series, namely, the imidazopyridines and the phenoxyalkylimidazoles ( 5 , 9 ). Recent work in the related organism Mycobacterium smegmatis suggests that Rv1339 is an atypical class II cAMP phosphodiesterase that has been linked to antibiotic tolerance ( 13 ). In addition, a P94L mutation in Rv1399 led to increased persistence in animal models and increased resistance to external stress in Mycobacterium canetti , which was proposed to be due to changes in cell wall permeability ( 14 ).…”
Section: Textmentioning
confidence: 99%
“…We have previously linked Rv1339 mutations to resistance to other QcrB inhibitor series, namely the imidazopyridines and the phenoxyalkylimidazoles (5,9). Recent work in the related organism Mycobacterium smegmatis suggests that Rv1339 is an atypical class II cAMP phosphodiesterase that has been linked to antibiotic tolerance (13). In addition a P94L mutation in Rv1399 led to increased persistence in animal models and increased resistance to external stress in Mycobacterium canetti, proposed to be due to changes in cell wall permeability (14).…”
Section: Moleculementioning
confidence: 99%